2016
DOI: 10.1504/ijex.2016.074263
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation in rectangular microchannels

Abstract: Entropy generation in a rectangular microchannel with fully developed steady gaseous flow at slip flow regime is studied. Two different thermal versions, uniform temperature (H1) and uniform heat flux (H2) on the walls, are considered. Analytically obtained expressions for temperature and velocity fields are used for entropy generation calculations. The effects of rarefaction, geometry, Peclet number Pe and group parameter Br/Ω on entropy generation (irreversibility) and local variation of entropy generation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Among the three channel shapes, square-shaped MCHS showed the lowest TEG for all Re and HFs. Kuddusi (2016) used two different thermal versions, uniform temperature and uniform HF on the walls to study the EG in the air flow through the rectangular MC. The EG calculations were made corresponding to the analytical expressions of the velocity and temperature profiles.…”
Section: Eg In Mcsmentioning
confidence: 99%
“…Among the three channel shapes, square-shaped MCHS showed the lowest TEG for all Re and HFs. Kuddusi (2016) used two different thermal versions, uniform temperature and uniform HF on the walls to study the EG in the air flow through the rectangular MC. The EG calculations were made corresponding to the analytical expressions of the velocity and temperature profiles.…”
Section: Eg In Mcsmentioning
confidence: 99%
“…Ebrahimi et al [21] analyzed increment in S gen,Fr for the case of nanofluid flow as a result of higher fluid viscosity at higher Reynold number (Re) due to lower bulk temperature of the coolant. The increase or decrease in the irreversibility is dependent on the value of Kn under uniform wall heat flux BC corresponding to an increase or decrease in the channel AR [22]. Cruz-Duarte et al [23] found the use of nanofluid in the laminar flow environment helpful in minimizing the entropy production of the system under the condition when the volume flow rate was considered as a design variable.…”
Section: Introductionmentioning
confidence: 99%
“…The studies in the micro-channel with slip flow and temperature jumps have been carried out by most of the researches [22][23][24][25][26][27][28][29], and they carried out useful findings. Hooman [30] performed entropy analysis under various boundary conditions through duct geometry and used a numerical technique.…”
Section: Introductionmentioning
confidence: 99%